Safety and efficacy of lumen-apposing metal stents for endoscopic ultrasound-guided drainage of pancreatic fluid collections: a systematic review and meta-analysis - Suresh Kumar, Vishnu Charan; Singh, Sahib; Moond, Vishali; Mohan, Babu P.; Aswath, Ganesh; Khan, Hafiz M. A.; Sapkota, Bishnu; Adler, Douglas G. (Endoscopy, 2024)
Endoscopic ultrasound (EUS)-guided drainage of pancreatic fluid collections (PFCs) has variable outcomes according to the type of lumen-apposing metal stent (LAMS) used. We aimed to perform a systematic review and meta-analysis of the available data.Online databases, including EMBASE, PubMed, and SCOPUS, were searched from inception to 30 January 2024. The outcomes of interest were technical success, clinical success, adverse events (AEs), and the need for endoscopic necrosectomy. Pooled estimates stratified by the type of stent (Axios, Nagi, or Spaxus), severity of bleeding, and type of PFC were calculated using a random-effects model. Heterogeneity was assessed by I2 values.37 studies were included in the final analysis. The pooled outcomes (95%CIs) for PFC drainage using the Axios, Nagi, and Spaxus stents, respectively, were: technical success 97.7% (96.4%–98.8%), 96.9% (94.6%–98.5%), 98.2% (94.4%–99.9%); clinical success 90.9% (88.7%–92.8%), 88.5% (79.9%–95.0%), 93.5% (91.0%–95.6%); total AEs 20.4% (16.6%–24.6%), 17.1% (8.3%–28.3%), 7.6% (3.6%–13.0); migration 4.2% (2.9%–5.7%), 7.8% (4.1%–12.4%), 0.9% (0.1%–2.8%); overall bleeding 7.0% (4.9%–9.5%), 4.4% (2.2%–7.4%), 1.8% (0.8%–3.3%); and endoscopic necrosectomy 54.5% (38.9%–69.7%), 16.0% (11.4%–21.3%), 19.9% (6.6%–38.1%). In terms of severity, moderate–severe bleeding was most common with all three stents. AEs were higher in patients with walled-off necrosis compared with pseudocysts. Substantial-to-considerable heterogeneity (I2 >60%) was present for total AEs for all of the stents.Our study shows good technical and clinical success rates with all three LAMSs for EUS-guided PFC drainage. Total AEs and bleeding were highest with the Axios stent and lowest with the Spaxus. Stent migration was highest with the Nagi stent and lowest with the Spaxus.